Correlations between subjective and objective features of nocturnal sleep and excessive diurnal sleepiness in patients with narcolepsy Correlação entre as características objetivas e subjetivas do sono noturno e a hipersonolência diurna em pacientes narcolepticos - Ulises Jiménez-Correa; Reyes Haro; Rosa Obdulia González; Javier Velázquez-Moctezuma (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To determine the correlations between excessive daytime sleepiness (EDS), assessed by the Epworth sleepiness scale (ESS), and the multiple sleep latency test (MSLT) and nocturnal sleep architecture features, clinical symptoms of narcolepsy (CSN) and subjective sleep quality (SSQ) in patients with narcolepsy. METHOD: Twenty three untreated patients were studied and compared with a matched control group. Diagnosis of narcolepsy was carried out employing a clinical interview, a polysomnographic (PSG) record, and an MSLT. RESULTS: Subjective number of awakenings was the SSQ indicator that best correlated with EDS (ESS and MSLT). Regarding clinical features, diurnal tiredness and sleep paralysis correlated with ESS values. Increase in ESS was related with decrease in total sleep time, SWS, and sleep onset latency. On the other hand, increase in MSLT was related with decrease in SWS. CONCLUSION: These data suggest that EDS in patients with narcolepsy could be impaired by disturbed nocturnal sleep. OBJETIVO: Determinar as correlações entre hipersonolência, avaliada pela escala de sonolência Epworth (ESE) e o teste múltiplo de latência do sono (TMLS) com a arquitetura do sono (AS), sintomas e qualidade subjetiva do sono em pacientes narcolepticos. MÉTODO: Comparou-se um grupo de vinte e tres pacientes narcolepticos sem tratamento com grupo controle. O diagnóstico de narcolepsia foi realizado por uma entrevista clinica, polissonografia e o TMLS. RESULTADOS: O número subjetivo de despertares foi o indicador com maior relação com a hipersonolência, o cansaço diurno e a paralisia do sono também foi correlacionados com a ESE.O aumento do índice na ESE foi correlacionado com uma diminuição do tempo total do sono, no sono de ondas lentas (SOL) e com a latência para o início do sono. O incremento na TMLS foi relacionado com diminuição do SOL. CONCLUSÃO: Os dados sugerem que a hipersonolência diurna em pacientes portadores de narcolepsia pode se correlacionar com as alterações da arquitetura do sono noturno.